Silicosis in Rubber Industry - เนติโรจนกุล, วิศิษฎ์; ลักขณาลิขิตกุล, เอกรินทร์; เจียมจรัสรังษี, วิโรจน์ (Journal of Preventive Medicine Association of Thailand, 2018)
A 36-year-old male with a previous history of pulmonary tuberculosis treatment presented with acute dyspnea. He was admitted and diagnosed with left pneumothorax. During admission, he developed recurrent pneumothorax. Right thoracotomy was performed at upper right and middle lung due to many blebs and bullae causing recurrent pneumothorax. Pathological examination showed coalesced fibrotic nodule containing large amount of silica particles with onion-skin liked appearance. He was finally diagnosed as having silicosis. He had worked in rubber industry for 8 years before developing lung diseases and had never worked in another industry that could expose silica, a cause of silicosis. Silica is used in manufacturing process in rubber industry. With literature review, there was no confirmed silicosis in rubber industry. Herein, we report the case with literature review of the possibility of silicosis in rubber industry.